Impedance Matching Simulation for Microstrip Antenna on Frequency 3.4-3.7 GHz Using Double Stub - Helfy Susilawati; Ahmad Fauzi; Akhmad Hasyim (Jurusan Teknik Elektro UIN Sunan Gunung Djati Bandung, 2020)
Impedance matching is an attempt to adjust the antenna impedance with the characteristic impedance of the transmission line. Impedance matching has functions to avoid reflected power from the antenna so that power cannot be received by the receiver. In this study, impedance matching was used double stub. The voltage standing wave ratio (VSWR) indicates how well the impedance matching is made. Simulation of this impedance matching will use to microstrip antenna on frequency 3.4 – 3.7 GHz. CST Studio Suite is used to simulating the antenna microstrip with double stub. Based on the result, this research shows that VSWR and return loss in single and double rectangular microstrip antenna have a better value if use impedance matching than without using impedance matching.